Pemikiran Tjokroaminoto dalam Praktik Sosialisme Islam Aktivis Peneleh - Jamil, Dzulkarnain; Sobari, Wawan; Maboddin, Muhtar (Fakultas Ushuluddin dan Filsafat UIN Sunan Ampel Surabaya, 2024)
This research explores the level of construction of Islamic Socialism in the Peneleh Activist Organization, both in terms of conceptual thinking and its application in the organization. This study aims to explore the ideology and value system that exists in thought to be a trigger for the revival of an organization’s moral spirit. This study used Berger's sociology of knowledge approach, which focuses on reality and knowledge. Meanwhile, this research applies qualitative case study methods. The study reveals that the practice of Islamic Socialism by Peneleh Activists is a follow-up to all big ideas regarding the unification of Religion and Ideology in today's social life. However, to make this happen, Peneleh Activists did not work alone. However, they succeeded in reaching an agreement in formulating the idea of Islamic Socialism in a cooperative scheme with other organizations. Thus, the construction of Islamic socialism carried out by Peneleh Activists not only focuses on reactualizing HOS Tjokroaminoto's ideas but also integrates new elements that are appropriate to current social and economic conditions and accommodate changes in practice and policy. This finding strengthens previous studies showing that Islamic Socialism is not just an intellectual movement, but also has a strong social dimension (İkiz, 2019). The construction of Islamic Socialism H.O.S Tjokroaminoto by Peneleh Activists has also expanded the interpretation of Islamic Socialism. Previously, Islamic Socialism tended to be a concept that only had the power of values as a guide to beliefs. This study reveals Islamic Socialism as a concept-building and practical step in organizational social activities. This study also contributes to building tactical steps toward achieving the ideals of Islamic socialism, namely independence (vrijheid-liberty), equality (gelijkheid-equalty), and brotherhood (broederschap-fraternity).